COMMUNITY ENGAGEMENT IN EDUCATION: FOSTERING SUSTAINABLE IMPACT THROUGH OUTREACH INITIATIVES - Wahyuniar, Wahyuniar; Asfahani, Asfahani; Suyuti, Suyuti; Sitopu, Joni Wilson (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
The education landscape has increasingly recognized the importance of community engagement in shaping sustainable educational impact. However, a need remains to explore and implement effective outreach initiatives that bridge educational disparities and empower communities. The service method uses a participatory action research (PAR) approach through participatory and collaborative methods, which is applied to identify specific needs in the educational community, involving teachers, students, parents, and the local community. Community service activities will be carried out from June to July 2023. This community engagement initiative aimed to foster sustainable educational impact through collaborative outreach initiatives, leveraging community strengths and resources. The initiative employed a participatory approach involving educators, community leaders, and stakeholders. Key methods included participatory mapping, culturally responsive pedagogies, and participatory decision-making processes. The initiative yielded transformative outcomes, including strengthened community partnerships, enhanced cultural inclusivity, and improved educational governance. Holistic development initiatives improved students' social cohesion, civic engagement, and leadership skills. The initiative underscores the potential of community engagement and outreach initiatives in fostering sustainable educational impact. Ongoing investment in partnerships, cultural responsiveness, and participatory practices is crucial for advancing inclusive and empowering educational environments.